Notkun róandi lyfja og svefnlyfja : upplýsingar frá apóteki og úr sjúkraskrám í Egilsstaðalæknishéraði 1986-1989 - Jóhann Ág. Sigurðsson; Gunnsteinn Stefánsson; Guðmundur Sverrisson; Þorsteinn Njálsson; Hjálmar Jóelsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Different methods have been used to study drug utilisation, i.e. analysis of a)sales statistics from pharmacies, producers and wholesales, b)prescriptions from pharmacies, c)medical records or d)by counting the number of tablets consumed by a patient over a certain period of time. Each of these methods has its advantages and disadvantages, but the reliability of the data and repeatability is of importance. Egilsstadir district is located on the east part of Iceland. The district is geographically isolated from the rest of the island with only one Health Centre and one pharmacy assessable to the inhabitants. A study was performed to measure the use of tranquillizers and sedatives/hypnotics from medical records and the sales statistics by the local pharmacy. The study period was 4 years, 1986-89, with an average study population of 2949. The medical records in the health centre are partly computerized and partly in a paper record. Through the computerized part of the record all individuals prescribed a tranquillizer and/or a hypnotic during the study period were identified. Their records were then pulled and names of drugs and number of tablets and quantity in mg recorded for each of the study year separately. The medical records and nurses diaries in the local nursing home were pulled and studied the same way. The pharmacy provided sales statistics for each of the study year, including names of drugs, number of tablets and quantity in mg sold. All the results are calculated as defined daily doses (DDD) per 1000 inhabitants per day. The results show good relationship between the sales statistics from the pharmacy and the recorded drug utilisation in the medical record from the local Health Centre. Differences are similar year after year. Somewhat higher figures from the pharmacy are considered mostly caused by prescription filled from persons travelling through the area or coming from the capital city from other ...